ERdj5 Reductase Cooperates with Protein Disulfide Isomerase To Promote Simian Virus 40 Endoplasmic Reticulum Membrane Translocation - Inoue, Takamasa (J Virol, 2015)
The nonenveloped polyomavirus (PyV) simian virus 40 (SV40) traffics from the cell surface to the endoplasmic reticulum (ER), where it penetrates the ER membrane to reach the cytosol before mobilizing into the nucleus to cause infection. Prior to ER membrane penetration, ER lumenal factors impart structural rearrangements to the virus, generating a translocation-competent virion capable of crossing the ER membrane. Here we identify ERdj5 as an ER enzyme that reduces SV40's disulfide bonds, a reaction important for its ER membrane transport and infection. ERdj5 also mediates human BK PyV infection. This enzyme cooperates with protein disulfide isomerase (PDI), a redox chaperone previously implicated in the unfolding of SV40, to fully stimulate membrane penetration. Negative-stain electron microscopy of ER-localized SV40 suggests that ERdj5 and PDI impart structural rearrangements to the virus. These conformational changes enable SV40 to engage BAP31, an ER membrane protein essential for supporting membrane penetration of the virus. Uncoupling of SV40 from BAP31 traps the virus in ER subdomains called foci, which likely serve as depots from where SV40 gains access to the cytosol. Our study thus pinpoints two ER lumenal factors that coordinately prime SV40 for ER membrane translocation and establishes a functional connection between lumenal and membrane events driving this process. IMPORTANCE PyVs are established etiologic agents of many debilitating human diseases, especially in immunocompromised individuals. To infect cells at the cellular level, this virus family must penetrate the host ER membrane to reach the cytosol, a critical entry step. In this report, we identify two ER lumenal factors that prepare the virus for ER membrane translocation and connect these lumenal events with events on the ER membrane. Pinpointing cellular components necessary for supporting PyV infection should lead to rational therapeutic strategies for preventing and treating PyV-related diseases.